Repercussions on oral cavity due to piercing use. Case report - Villalobos Montero, Alexander (2018)
The corporal piercing is defined as the penetration of an ornament to holes made in the skin and/or mucosa, using an acute instrument that creates an opening through which the ornament can be applied. The use of oral piercing in young people is gaining strength because it is considered an expression of art in the oral cavity. Within the most common areas to place them are the back of the tongue and the lower lip. This fashion can become very harmful to oral health because it can cause infections and in the worst cases cause complications that place life at risk. In this article, we describe the characteristics of damage caused in the oral cavity for use of a tongue piercing. A 29-year-old male, patient with coronal fracture and pain to cold and heat in tooth 3.6 was reported, as well as vertical bone loss in teeth 4.1 and 4.6; the case was resolved through non-surgical endodontic treatment and referred to periodontics service. We conclude that the use of lingual piercing can be associated with coronal fractures and periodontal problems.